T-cell depleted haploidentical hematopoietic cell transplantation for pediatric malignancy - Takahashi, Takuto; Prockop, Susan E. (Frontiers in Pediatrics, 2022)
Access to allogenic hematopoietic cell transplantation (HCT), a potentially curative treatment for chemotherapy-resistant hematologic malignancies, can be limited if no human leukocyte antigen (HLA) identical related or unrelated donor is available. Alternative donors include Cord Blood as well as HLA-mismatched unrelated or related donors. If the goal is to minimize the number of HLA disparities, partially matched unrelated donors are more likely to share 8 or 9 of 10 HLA alleles with the recipient. However, over the last decade, there has been success with haploidentical HCT performed using the stem cells from HLA half-matched related donors. As the majority of patients have at least one eligible and motivated haploidentical donor, recruitment of haploidentical related donors is frequently more rapid than of unrelated donors. This advantage in the accessibility has historically been offset by the increased risks of graft rejection, graft-versus-host disease and delayed immune reconstitution. Various ex vivo T-cell depletion (TCD) methods have been investigated to overcome the immunological barrier and facilitate immune reconstitution after a haploidentical HCT. This review summarizes historical and contemporary clinical trials of haploidentical TCD-HCT, mainly in pediatric malignancy, and describes the evolution of these approaches with a focus on serial improvements in the kinetics of immune reconstitution. Methods of TCD discussed include in vivo as well as ex vivo positive and negative selection. In addition, haploidentical TCD as a platform for post-HCT cellular therapies is discussed. The present review highlights that, as a result of the remarkable progress over half a century, haploidentical TCD-HCT can now be considered as a preferred alternative donor option for children with hematological malignancy in need of allogeneic HCT.